PPM Pembuatan Dinding Peredam Suara dari Sampah Daun pada Sekolah Adiwiyata di SMP Negeri 24 Kota Semarang - Masturi Masturi; Dante Alighiri; Fifin Dewi Ratnasari; Kurnia Galuh Candra Kirana; Fadhillah Choirunnisa; Ratih Sukmawati (Universitas Negeri Semarang, 2024)
The large amount of leaf litter in the partner environment of SMP Negeri 24 Semarang City as one of the prospective Adiwiyata schools will in the long term become a problem that requires more innovative and scientific solutions and handling. On the other hand, the problem of increasing wood utilization requires a more serious solution. The solution offered by the implementing team to this problem is through processing leaf waste into composite material which is expected to be a substitute for wood which can be applied as a sound absorber in the partner environment of SMP Negeri 24 Semarang. Leaf waste and silica together with polyurethane (PU) polymer are molded at a certain pressure and temperature for a certain time to obtain a material with the most optimum mechanical strength. This activity has been carried out well, the partners involved (in this case students and teachers) have succeeded in making composites from leaf waste which is abundant in the school environment. This composite will later be applied as a damper in one of the rooms at SMP 24 Semarang.